KAPAN PENGAJARAN BAHASA INGGRIS DI INDONESIA LEPAS DARI WILAYAH ABU-ABU? Sebuah Refleksi atas Tarik Ulur Proses Akuisisi dan Obsesi Dalam Pengajaran Bahasa Inggris Di Indonesia - Achmat, Ali (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2013)
This study aims to reveal the missing link of the real process and the intended output of English teaching and learning process in the classroom. Acquisition process as an important element to achieve the intended output does not become the first to be developed in the real process of English teaching and learning process in the classroom. In contrast, the teachers concern more on the process of teaching the way to do final examination to achieve the passing-grade standard.